Ayurvedic Prakriti Classification and Its Correlation with Inflammatory Gene Expression Profiles - Dr. Sukhdevsinh Kamariya; Dr. Yogita B. Mandle; Dr. Priti Tatyasaheb Mane (The Bioscan, 2026)
Prakeet Ayurvedic theory of Prakriti means the individual psychophysiological constitution identified by Vata, Pitta, and Kapha, and is an in-depth explanation of individual variations in disease and health. The molecular correlates of Prakriti are explored in this study by utilizing the Ayurvedic phenotyping and the application of contemporary measures of transcriptomic analytics, such as genome-wide inflammatory gene expression profiles. The study provides the biological insights that can help explain the natural variation in inflammatory vulnerability and metabolic adjustment through correlating the different types of Prakriti with variable expression of cytokine regulatory networks, NF- 0B signaling pathways and immune-modulatory genes. We conclude that Prakriti-specific signature of gene may be used as biomarkers of customized preventive care and specific Ayurveda-based therapy. It is an integrative systems biology approach that reconciles the traditional wisdom and modern molecular science, opening a new individualized paradigm of health prediction and disease modulation based on the ancient wisdom and the evidence in genomes.